An objective bone conduction verification tool using a piezoelectric thin-film force transducer - Nie, Yafei; Sang, Jinqiu; Zheng, Chengshi; Xu, Jian; Zhang, Fangjie; Li, Xiaodong (Frontiers in Neuroscience, 2022)
All hearing aid fittings should be validated with appropriate outcome measurements, whereas there is a lack of well-designed objective verification methods for bone conduction (BC) hearing aids, compared to the real-ear measurement for air conduction hearing aids. This study aims to develop a new objective verification method for BC hearing aids by placing a piezoelectric thin-film force transducer between the BC transducer and the stimulation position. The newly proposed method was compared with the ear canal method and the artificial mastoid method through audibility estimation. The audibility estimation adopted the responses from the transducers that correspond to the individual hearing thresholds and three different input levels of pink noise. Twenty hearing impaired (HI) subjects without prior experience with hearing aids were recruited for this study. The measurement and analysis results showed that the force transducer and ear canal methods almost yielded consistent results, while the artificial mastoid method exhibited significant differences from these two methods. The proposed force transducer method showed lower noise level and less affected by the sound field signal when compared with other methods. This indicates that it is promising to utilize a piezoelectric thin-film force transducer as an in-situ objective measurement method of BC stimulation.